FORMULATION OF NANOEMULGEL CONTAINING EXTRACT OF IMPATIENTS BALSAMINA L. AND ITS ANTIBACTERIAL ACTIVITY - WIKANTYASNING, ERINDYAH RETNO; SETIYADI, GUNAWAN; PRAMUNINGTYAS, RATIH; KURNIAWATI, MEGA DWI; YEE HO, CHAI (International Journal of Applied Pharmaceutics, 2023)
Objective: This study aimed to optimize the nanoemulgel formulation for balsam leaves (Impatients balsamina L.) extract and determine its antibacterial activity. Methods: Balsam leaves were extracted using the maceration method using ethanol. The nanoemulsion of balsam leaves ethanol extract was prepared with various oil, surfactants, and co-surfactant concentrations. Characterization was conducted on the nanoemulsion formed, including transmittance, droplet size, polydispersity index, and zeta potential. The chosen nanoemulsion formula was then transformed into a gel preparation using various gelling agent concentrations, i.e., Carbopol 940 and chitosan, and optimized using the Design-Expert v13 software with the simplex lattice design method. Results: The study discovered the optimum nanoemulgel formula with a desirability value of 0.859. The ratio of Carbopol 940 with chitosan was 1.38% and 0.12%w/w, respectively, with an antibacterial activity inhibition zone against S. epidermidis of 22±2 mm in diameter. Conclusion: The observed responses closely matched the predicted values provided by the optimization method. The optimized nanoemulgel formulation has the potential to develop as an antibacterial dosage form.